The Relationship between Using of an Intelligent Tutoring System and Class Achievement in a Basic Mathematics Course - Haraty, Ramzi Ahmed; Sharif, Abbass I. (International Journal of Emerging Technologies in Learning (iJET), 2008)
In this paper, we present a case in which we integrated an intelligent tutoring system- ITS- in a basic mathematics course. The proposed ITS â??PrivateTutor- is dynamic, web-based, adaptive, and interactive. It is composed of six different modules; each has a distinct function: student, domain, question, communication, expert, and controller modules. The purpose of this system is not to eliminate the role of human teachers, but to complement their effort in reaching all students and having one-to-one tutoring approach instead one-to-many. An experiment was conducted in order to study the effectiveness of PrivateTutor on class achievement. Students who were enrolled in a â??Basic Mathematics